Environment-Based Budget as an Effort to Optimize the Citarum Harum Program - Putri, Rizqya Nafila; Astriani, Nadia; Widjayani, Supraba Sekarwati (PAMALI: Pattimura Magister Law Review, 2025)
Introduction: The importance of an environment-based budget in an effort to optimize the revitalization program of the Citarum River, known as Citarum Harum. The program aims to address the serious problem of river pollution, but has not achieved optimal results because sustainable budgets have not been fully implemented.Purposes of the Research: The purpose of this research is to examine why environment-based budgeting is still not a priority in program implementation, and how this affects the overall and long-term success of the program.Methods of the Research: Using the method of policy analysis and evaluation of program implementation, this study reveals that the misalignment between budget policies and environmental needs has hampered the effectiveness of revitalization efforts.Results Main Findings of the Research: Key findings suggest that delays in the adoption of environmentally-oriented budgets result in slow, suboptimal, and unsustainable river recovery. The impact of these findings highlights the urgency of comprehensively integrating environmentally-based budgets to accelerate the recovery of river ecosystems and ensure the long-term sustainability of the program. In addition, the study also emphasizes that without proper and consistent budget support, revitalization programs such as Citarum Harum will continue to face significant challenges in achieving the expected environmental goals. In conclusion, budget management that is aligned with environmental conservation efforts is key to increasing the success of future environmental programs, including the revitalization of the Citarum River and other ecosystem restoration efforts in Indonesia.